2015
DOI: 10.1590/1806-9282.61.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the length of hospital stay after total knee arthroplasty: influence of femoral and sciatic nerve block

Abstract: Carvalho Jr. lh et al. 40rev assoC Med bras 2015; 61(1):40-43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…On the other hand, these parameters are not well studied for the management of acute exacerbations of chronic neuralgiform pain. Most data on the relationship between PNB use and length of stay comes from orthopedic surgery studies that evaluate the benefits of PNBs in the setting of postoperative pain . A review in the Cochrane Database showed very‐low‐quality evidence for PNBs to decrease length of stay and low‐quality evidence to increase patient satisfaction when compared to systemic analgesia alone in the setting of elective hip replacement …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these parameters are not well studied for the management of acute exacerbations of chronic neuralgiform pain. Most data on the relationship between PNB use and length of stay comes from orthopedic surgery studies that evaluate the benefits of PNBs in the setting of postoperative pain . A review in the Cochrane Database showed very‐low‐quality evidence for PNBs to decrease length of stay and low‐quality evidence to increase patient satisfaction when compared to systemic analgesia alone in the setting of elective hip replacement …”
Section: Discussionmentioning
confidence: 99%
“…A systematic review, however, did not support these studies [20]. And femoral and sciatic nerve block promoted shorter hospital staying and superior postoperative pain control up to 12 h compared to femoral block plus local infiltration, even though local infiltration could preserve quadriceps function in the immediate postoperative period as an advantage [23–25]. …”
Section: Discussionmentioning
confidence: 99%
“…Prolonged length of stay (LOS) has been associated with increased rates of nosocomial infections, medical complications, and poorer surgical and patient-reported outcomes (PROMs) [1][2][3]. Factors that impact LOS in elective orthopedics have been identified, including patient factors (eg, BMI, smoking, age, sex, comorbidities, social support) [4][5][6][7][8], procedure factors (eg, surgeon experience, drain use, use of blocks or local anesthetic infiltration) [9][10][11][12], postprocedural protocols (eg, early mobilization) [6], and hospital factors (eg, volume, orthopedics-specialized ward) [13,14].…”
Section: Introductionmentioning
confidence: 99%